PENGARUH PENDEKATAN DEEP LEARNING MELALUI FLASHCARD UNTUK MENINGKATKAN KREATIVITAS PELAJARAN MATEMATIKA - Kharisma, Viona Nova; Rida Fironika, K (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study focuses on the effect of deep learning approach through flashcard media to improve student creativity in mathematics subjects of grade III of SD N Tambakrejo 01. The purpose of this study was to determine the effect of deep learning approach through flashcard media to improve student creativity in mathematics subjects of grade III of SD N Tambakrejo 01. This study used a Pre-Experimental Design. The study with only one test class, without a comparison or control class. This research design used a one-group pre-test post-test design, where the research objects will take tests before and after receiving treatment. The population and sample in this study were grade III of SD N Tambakrejo 01 using probability sampling techniques. Based on the research results, the deep learning approach through flashcards has been shown to enhance student creativity, Furthermore, the average pre-test score was 46.77, and after the treatment, the average post-test score increased to 71.25. The obtained average scores were further strengthened by a paired sample t-test to determine the effect of the independent variable, the deep learning approach, on the dependent variable of student creativity. The test yielded results as shown in the sig. (2-tailed) column <α 0.05, indicating that Ho is rejected. Therefore, it can be concluded that sig. (2-tailed) <0.001, indicating that sig. (2-tailed) <= 0.05, indicating that Ho is rejected and Ha is accepted. Thus, the deep learning approach through flashcards has been shown to enhance the creativity of third-grade mathematics students